The Efficacy of Music for Emotional Wellbeing During the COVID-19 Lockdown in Spain: An Analysis of Personal and Context-Related Variables - Martínez-Castilla, Pastora; Gutiérrez-Blasco, Isabel M.; Spitz, Daniel H.; Granot, Roni (Frontiers in Psychology, 2021)
The strict lockdown experienced in Spain during March-June 2020 as a consequence of the COVID-19 crisis has led to strong negative emotions. Music can contribute to enhancing wellbeing, but the extent of this effect may be modulated by both personal and context-related variables. This study aimed to analyze the impact of the two types of variables on the perceived efficacy of musical behaviors to fulfill adults’ emotional wellbeing-related goals during the lockdown established in Spain. Personal variables included age, gender, musical training, personality, resilience, and perception of music’s importance. Contextual variables referred to living in a region with a high COVID-19 impact, perception of belonging to a risk group, being alone, having caring responsibilities during confinement, and amount of time of music listening as compared to prior to the crisis. The study was conducted retrospectively during August-December 2020, when the strict lockdown was over in Spain. An online survey was disseminated among the general population and groups of musicians, and the answers of 507 adults (from 18 years on, 73.9% females, 51.3% musically trained adults) were analyzed. Only personal, but not COVID-19 context-related variables, showed an impact on music’s efficacy. The youngest age group of adults and those with musical training reported the highest efficacy of music for wellbeing enhancement, and music’s importance was found to be the main significant predictor of music’s perceived efficacy. Our findings suggest that the people who have been reported to be emotionally more vulnerable during the lockdown, due to either a strong impact on their daily lives or their lower resilience, perceive a higher benefit from musical behaviors. Being musically trained, even for a small number of years, also leads to a perception of higher efficacy of music for the achievement of emotional wellbeing goals. However, this effect is explained by the musically trained individuals’ higher perception of music’s importance. Although musical behaviors can be generally considered as important for wellbeing enhancement, our study highlights who are the potential individuals who could benefit the most from music-related activities for obtaining better levels of wellbeing, at least within the current context of the COVID-19 crisis.